The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1600-0536.1996.tb02142.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyldibromoglutaronitrile is an important contact allergen in The Netherlands

Abstract: From 15 May to 15 December 1994, 2943 patients suspected of having contact dermatitis (1955 women, 988 men) were patch tested with methyldibromoglutaronitrile 0.3%, 0.1% and 0.05% pet. 119 patients (4.0%; women 4.1%), men 3.8%) proved to be allergic. 71% of the reactions were considered to be relevant. In 2/3 of the patients, causative products were cosmetics, in 1/3 moistened toilet tissues. Testing with methyldibromoglutaronitrile at lower concentrations (0.05% and 0.1%) and with commercial allergens (Euxyl®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 8 publications
2
51
0
Order By: Relevance
“…Since then, allergic contact dermatitis has been reported from MDBGN in different products such as soap, cleansing milk, shampoos, moisturizers, ultrasonic gel, moistened toilet paper, sunscreen lotion, detergents, and eye gel. de Groot et al showed an increase in the frequency of positive test reactions to MDBGN in the Netherlands from 0.5% in 1991 to 4% in 1994 (79). Similarly, the levels of patch test sensitivity to MDBGN increased from 0.7% in 1991 to 3.5% in 2000 in a European multicentre analysis (57).…”
Section: Methyldibromo Glutaronitrile Euxylmentioning
confidence: 95%
“…Since then, allergic contact dermatitis has been reported from MDBGN in different products such as soap, cleansing milk, shampoos, moisturizers, ultrasonic gel, moistened toilet paper, sunscreen lotion, detergents, and eye gel. de Groot et al showed an increase in the frequency of positive test reactions to MDBGN in the Netherlands from 0.5% in 1991 to 4% in 1994 (79). Similarly, the levels of patch test sensitivity to MDBGN increased from 0.7% in 1991 to 3.5% in 2000 in a European multicentre analysis (57).…”
Section: Methyldibromo Glutaronitrile Euxylmentioning
confidence: 95%
“…Later, the local lymph node assay (LLNA) and cumulative contact enhancement test showed that multiple topical applications of methyldibromo glutaronitrile resulted in sensitization [26]. Surveillance data showed in the late 1990s that the prevalence of contact allergy to methyldibromo glutaronitrile increased as its use gradually became more widespread in European cosmetic products and toiletries [5,9,[27][28][29]. The prevalence of contact allergy to methyldibromo glutaronitrile in Europe increased from 0.7% in 1991 to 3.5% in 2000 in consecutive patch-tested patients with contact dermatitis [9].…”
Section: Contact Allergy To Methyldibromo Glutaronitrilementioning
confidence: 99%
“…However, this prevalence increased in 1994 [22] to 4% in a multicentre investigation of 2,943 patients tested with MDBGN 0.05%, 0.1% and 0.3% pet., soy lecithin 5% being added to obtain homogeneous dispersions.…”
Section: Frequency Of Contact Sensitisation To Euxyl K400mentioning
confidence: 99%
“…They had repeatedly used moistened toilet tissue, this habit presumably being the cause of their sensitisation. In 1994, De Groot et al [22] reviewed 2,943 patients suspected of having contact dermatitis and patch tested with MDBGN. Approximately one third (30 patients) of the relevant positive patch tests (84 patients) had moistened toilet tissue as their cause.…”
Section: Contact Allergy To Euxyl K400 In Cosmetics and Skin Creamsmentioning
confidence: 99%
See 1 more Smart Citation